Forms and Meanings of Stative Verbs in Progressive Tense: a Corpus Linguistics Research - Upi Laila Hanum (Hasanuddin University, 2018)
AbstractSemantics is the field of linguistic concerned with the study of meaning in language. The aims of the research are to analyze the forms and meanings of the stative verbs in progressive tense in corpora. The data of this research were obtained from Corpus of Contemporary American English (COCA) and British National Corpus (BNC). The data of the corpora used descriptive qualitative. The result of the research shows that the stative verbs are found and used in progressive tense. The stative verbs appeared in all types of progressive tense except future perfect progressive. The use of the stative verbs in progressive tense took place due to overgeneralization in the use of the native speakers’ form of American and British English. The stative verbs in progressive tense used to express temporariness, emotiveness, comprehension and mixed categories of meaning; temporariness and emotiveness, temporariness and tentativeness. Temporariness meaning almost appeared in all types of progressive. Stative verbs in progressive tense indirectly stated temporariness in stative sense of meaning, is contrary to the rules of English grammar.